Cardiovascular risk communication strategies in primary prevention. A systematic review with narrative synthesis. (19th June 2022) - Schulberg, Stacey D.; Ferry, Amy V.; Jin, Kai; Marshall, Lucy; Neubeck, Lis; Strachan, Fiona E.; Mills, Nicholas L.
Abstract: Aim: To evaluate the effectiveness of cardiovascular risk communication strategies to improve understanding and promote risk factor modification. Design: Systematic review with narrative synthesis. Data sources: A comprehensive database search for quantitative and qualitative studies was conducted in five databases, Cumulative Index to Nursing and Allied health Literature (CINAHL), Medical Literature Analysis and Retrieval System Online (MEDLINE), EMBASE, Applied Social Sciences Index and Abstracts (ASSIA) and Web of Science. The searches were conducted between 1980 and July 2019. Review methods: The systematic review was conducted in accordance with Cochrane review methods. Data were extracted and a narrative synthesis of quantitative and qualitative results was undertaken. Results: The abstracts of 16, 613 articles were assessed and 210 underwent in‐depth review, with 31 fulfilling the inclusion criteria. We observed significant heterogeneity across study designs and outcomes. Nine communication strategies were identified including numerical formats, graphical formats, qualitative information, infographics, avatars, game interactions, timeframes, genetic risk scores and cardiovascular imaging. Strategies that used cardiovascular imaging had the biggest impact on health behaviour change and risk factor modification. Improvements were seen in diet, exercise, smoking, risk scores, cholesterol and intentions to take preventive medication. Conclusion: A wide range of cardiovascular risk communication strategies has been evaluated, with those that employ personalized and visual evidence of current cardiovascular health status more likely to promote action to reduce risk. Impact: Future risk communication strategies should incorporate methods to provide individuals with evidence of their current cardiovascular health status.